2006
DOI: 10.1111/j.1365-2036.2006.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between nadolol and 5‐isosorbide mononitrate vs. endoscopic band ligation plus sclerotherapy in the prevention of variceal rebleeding in cirrhotic patients: a randomized controlled trial

Abstract: SUMMARY BackgroundAfter variceal bleeding, cirrhotic patients should receive secondary prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…There were also 4 studies 31-34 comparing pharmacotherapy with ligation and 3 studies 35-37 assessing the combined effect of pharmacotherapy and ligation and that of ligation alone. Romero et al 38 organized the only study that compared the efficacy of pharmacotherapy with that of the combination of sclerotherapy and ligation. In the current meta-analysis, patients receiving either sclerotherapy or band ligation were categorized into an endoscopy group.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also 4 studies 31-34 comparing pharmacotherapy with ligation and 3 studies 35-37 assessing the combined effect of pharmacotherapy and ligation and that of ligation alone. Romero et al 38 organized the only study that compared the efficacy of pharmacotherapy with that of the combination of sclerotherapy and ligation. In the current meta-analysis, patients receiving either sclerotherapy or band ligation were categorized into an endoscopy group.…”
Section: Data Extractionmentioning
confidence: 99%
“…The b-blocker used was either propranolol or nadolol in these studies, with most of the trials opting for propranolol. Nadolol in combination with nitrates was used in 4 trials, 18,31,32,38 and sucralfate was used in 1 study. 33 However, nadolol alone was used in 2 studies.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…It is still unknown whether drug therapy is superior to EBL for preventing variceal rebleeding. Several randomized controlled trials have shown different results [6][7][8][9] . Meta-analyses can statistically combine the results of several studies and resolve discrepancies among single studies.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen (69%) RCTs reported the concealment of randomization via sealed opaque envelopes or using central randomization; and 2 trials stopped early [5,27]. Given that blinding is difficult for trials involving endoscopic procedures, only one eligible trial [35] used the double-blinded design. The blindness status of most RCTs was not informed, regardless of participants, health care providers, data collectors, or outcome assessors.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Six trials [5,22,27,35,37,42] were multicenter trials. Beta-blockers were administrated in 9 trials, including nadolol used in 6 trials [5,6,12,27,35,41] and propranolol in the other 3 [20,24,42]. Followup time of 4 trials [23,33,40,42] was less than 3 months, but there were 15 RCTs followed up for 1 year or more.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%